Serum Histatin Levels in COVID-19: Association With Disease Severity and Immune Status - Aydin, Umut; Duzenci, Deccane; Akkoc, Ramazan Fazil; Karatas, Ahmet (Wiley, 2026)
Histatins are histidine-rich antimicrobial peptides with emerging immunomodulatory properties; however, their systemic behavior across the clinical spectrum of COVID-19 remains unknown. We aimed to characterize serum histatin levels in patients with mild COVID-19 (without pneumonia) and severe COVID-19 (with pneumonia) and to explore factors potentially associated with their variation. Ninety individuals were prospectively enrolled: healthy controls (n = 30), patients with mild COVID-19 (without pneumonia (n = 30), and patients with severe COVID-19 (with pneumonia receiving corticosteroid therapy (n = 30). Serum histatin-1, histatin-3, and histatin-5 concentrations were quantified by ELISA. Group comparisons were performed using Kruskal-Wallis and Mann-Whitney U tests; correlations were assessed using Pearson coefficients. Histatin-1 did not differ among groups (p = 0.161). Both histatin-3 and histatin-5 were significantly reduced in mild COVID-19 compared with controls (p = 0.004 and p = 0.002, respectively). Unexpectedly, patients with severe COVID-19, all of whom were receiving corticosteroids, did not exhibit further histatin reductions; their levels were comparable to controls and significantly higher than the mild group (histatin-3 p = 0.016; histatin-5 p = 0.028). Histatin-3 correlated significantly with ferritin (r = 0.413; p = 0.009), D-dimer (r = 0.369; p = 0.021), and albumin (r = -0.330; p = 0.018). SARS-CoV-2 infection without pneumonia was associated with significantly lower serum histatin-3 and histatin-5 levels. In contrast, histatin levels were preserved in patients with severe COVID-19 and pneumonia who were receiving corticosteroid therapy. Because of the cross-sectional design, this finding should be interpreted as an association rather than evidence of a treatment effect. The observed correlations between histatin-3 and ferritin, D-dimer, and albumin further suggest that histatin-3 may be linked to acute-phase and inflammatory responses during COVID-19.
Keywords: Antimicrobial Peptides; Biomarkers; Corticosteroids; Covid-19 Severity; Histatins; Inflammation; Sars-Cov-2